Peran Dewan Pengawas Syariah Terhadap Perkembangan Bisnis Koperasi Syariah di SMA Negeri 4 Praya Kabupaten Lombok Tengah Tahun 2021/2022 - Muhamad Zaini; Zaenudin Mansyur; Baiq Ratna Mulhimmah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The Sharia Cooperative at State Senior High School 4 Praya has recorded remarkable profit increases for three consecutive years. In 2020, they achieved a profit of IDR 90,045,658, which then saw rapid growth in 2021, reaching IDR 109,491,289, marking a growth of IDR 19,445,631. Not stopping there, the year 2022 was an even more impressive achievement with profits reaching IDR 164,032,600, indicating strong performance and the ability to maintain significant growth momentum. This study indicates that the factors influencing the business development of the Sharia Cooperative at State Senior High School 4 Praya include: a) Member Participation, b) Management Professionalism, c) External Factors. In the context of the cooperative's success at State Senior High School 4 Praya, it is heavily influenced by the complex interaction between member participation, management professionalism, and external factors. The role of the Sharia Supervisory Board in enhancing the business development of the Sharia Cooperative at State Senior High School 4 Praya includes: a) Supervisor, b) Advisor, c) Marketer, d) Supporter, e) Player. In the context of supervision and control, the Sharia Supervisory Board not only monitors but also provides guidance and support to ensure that the Sharia Cooperative can achieve its goals by adhering to Sharia principles, enhancing business development, and providing benefits to its members. The success of the Sharia Supervisory Board in its roles significantly contributes to the growth and sustainability of the Sharia Cooperative at State Senior High School 4 Praya.